The Semiotics of Sacred Consumption: A Saussurean Analysis of Marjan’s Ramadan Advertising on Instagram - Inosensius Enryco Mokos; Hinhin Agung Daryana; Moch. Gigin Ginanjar; Denhaz Nurul Hakim (4, 2026)
This research investigates the intricate construction of visual and verbal meanings within Marjan’s Instagram advertisements during the 2024 Ramadan season and explores how these semiotic configurations stimulate consumer purchase intention. Adopting a qualitative paradigm underpinned by Ferdinand de Saussure’s structuralist semiotics, the study deconstructs the dyadic relationship between signifiers and signifieds in digital promotional content. Systematic observation of visual markers, including the brand logo, the signature red syrup bottle, young coconut motifs, Ramadan lanterns, and desert landscapes, reveals a deliberate orchestration of brand identity, sensory freshness, spiritual enlightenment, and cultural nostalgia. Concurrently, verbal signifiers such as the slogan